A comparative study of teachers perspectives in city center of Fars and its remotest towns or villages toward high schools' Junior Secondary book - Bagheri, Masoud; Karampour, Fatemeh (JOURNAL OF ADVANCES IN LINGUISTICS, 2015)
Regarding the textbook evaluation a whole slew of studies are done and each of which is taken into account different aspects of the books. Since the book entitled Prospectone is a recently released one and there was no investigation about it the researcher decided to scrutinize it. The investigator administered a questionnaire and a semi-structured interview. The study was intended to investigate and compare the teachers perspectives in center of Fars Province and in its remotest villages or towns such as Lamerd, Mohr, Galedar, Ashkanan and Alamarvdasht. A total population of 100 people participated in this research. To gather the data, Litz questionnaire was used. Regarding the obtained findings from the questionnaires and semi-structures interviews, it revealed that the teachers in remotest villages ran through more difficulties. And it is believed that most of their problems are due to the lack of background knowledge. The learners who attended grade7th had no background knowledge in English. As Krashen(1975) stated the input that the learners receive should be comprehensible and one level higher than the student immediate knowledge.Â  Although most of the learners in Fars province participated in extra curricular classes, mostly institute classes, the students in rural places had never attended in any. Another revealed result is that there was not any balance between the skills in the book and most of the empathies are on oral skills. To put all the aforementioned statements into a nutshell, it can be said that there is a big gap between students current knowledge in Fars province and the ones in villages.